2021
DOI: 10.1186/s40814-021-00781-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and feasibility testing of a play-based psychosocial intervention for reduced patient stress in a pediatric care setting: experiences from Pakistan

Abstract: Background Hospitalization can be a source of great stress for children and their families. In high-income countries, there are specialized staff to help children cope using different techniques including play. However, it is a major challenge in low and middle-income countries (LMIC) due to financial constraints and untrained human resource. The objective of study was to develop and test the feasibility and acceptance of a psychology trainee-delivered model postulated on employing play as a me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…They found that reducing the level of stress in mothers of the preterm infants could help enhance the mother-newborn relationship and decrease mothers 'dissatisfaction. 32 Therefore, the problem-solving technique could be an acceptable structure to design postpartum care programs and it could be considered by health providers in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…They found that reducing the level of stress in mothers of the preterm infants could help enhance the mother-newborn relationship and decrease mothers 'dissatisfaction. 32 Therefore, the problem-solving technique could be an acceptable structure to design postpartum care programs and it could be considered by health providers in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is a private elite setting, relatively affluent families seek consultation. Data from previous work indicate about half of the mothers' accessing pediatric services have completed 10 years of education or more (28). Patients are primarily from the city and surrounding urban and rural areas within the province of Sindh.…”
Section: Settingmentioning
confidence: 99%
“…All families can positively contribute toward the development of their child and may just need minimum coaching. The first author is a certified trainer for implementing the CCD module and has successfully used it as an intervention for in-patient children and families in collaboration with psychology trainees as the delivery staff (28).…”
Section: The Family Support Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a private tertiary hospital in Pakistan, a play-based psychosocial intervention programme for children between birth and 6 years was initiated in 2018 years with the aim to reduce stress for the child and the family (Rasheed, Bharuchi, Mughis, & Hussain, 2021). The study was conducted to further strengthen the case for introducing the intervention programme rationalizing that such interventions can not only reduce stress to improve patient and family experience but can also act as a buffer against the effects of illness on health-related quality of life (developmental outcomes) as indicated in literature from high-income countries.…”
mentioning
confidence: 99%